Commemorating and Forgetting: Political Memory of the Battle of Surabaya throughout Old Order and New Order Regimes in Indonesia (1951 - 1988) - Mohammad Masrudin Firdiyansyah (UIN Imam Bonjol Padang, 2024)
The gallantry of the people of Surabaya in resisting Allied forces in 10th November 1945 led the government to designate that date as Heroes’ Day. Various ceremonies are held and monuments are built to preserving the memory of the battle. However, the construction of this historical memory is not without its own interests. This research examines how historical memory of the Battle of Surabaya was constructed throughout the administration of Sukarno and Suharto, why the memory was erected and what aspect was deliberately forgotten. Employing historical methodology, this research shows Sukarno leveraged these historical narrtives to foster nationalism and enhance Indonenisa’s international standing. Under the regime of Suharto, the construction of historical memory was similarly used to promote his political agendas, spread anti-communism and legitimate military role. Both regimes sought to conceal the killings of civilians and the disparities between central administration and local Surabaya residents due to beliefs that it would undermine nationalism and heroic narrative.